Newman, Catholicity, and the Church Today: On the Development of Christian Principles through Dialogue with the World - Cimorelli, Christopher (Religions, 2021)
This article explores the following question: Given the Roman Catholic Church’s present-day teaching on catholicity, how can St. John Henry Newman’s historically conscious, imaginative view of catholicity assist Catholic Christians today in understanding the concept faithfully, but in a manner ‘open’ to its potential development in an age of shifting metaphysics? After (1) an introduction to the topic and challenges to the notion of catholicity today, this article then (2) analyzes the present-day view of catholicity as a mark of the church according to the ‘Catechism of the Catholic Church’, noting areas of development as well as limitations. The article then (3) investigates Newman’s understanding of catholicity within his sacramental and imaginative worldview. Newman’s understanding of the development of principles and doctrines is particularly relevant for a consideration today of how the church’s view of catholicity might authentically develop from a dialogue between religion and science. The article then (4) synthesizes results in a concluding section that indicates how the fruits of the preceding analysis could be realized through eco-theological dialogue.